2020
DOI: 10.1111/bjh.16910
|View full text |Cite
|
Sign up to set email alerts
|

ROR1 is an accurate and reliable marker of minimal residual disease in chronic lymphocytic leukaemia

Abstract: Additional supporting information may be found online in the Supporting Information section at the end of the article. Data S1. Detailed description of the methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…In 2018, Rawstron et al published a consensus recommending a panel of markers, including ROR1 along with CD43, CD79b, CD81, CD200, and CD10, and showed the utility and importance of ROR1 in refining the diagnosis of borderline cases (Rawstron et al, 2018). De Propris and colleagues have demonstrated that the expression and MFI of ROR1 were preserved in CLL cells during and after different treatment (De Propris et al, 2020). These properties make ROR1 an attractive candidate for MRD monitoring in combination with other core molecules, as proposed by ERIC.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Rawstron et al published a consensus recommending a panel of markers, including ROR1 along with CD43, CD79b, CD81, CD200, and CD10, and showed the utility and importance of ROR1 in refining the diagnosis of borderline cases (Rawstron et al, 2018). De Propris and colleagues have demonstrated that the expression and MFI of ROR1 were preserved in CLL cells during and after different treatment (De Propris et al, 2020). These properties make ROR1 an attractive candidate for MRD monitoring in combination with other core molecules, as proposed by ERIC.…”
Section: Discussionmentioning
confidence: 99%
“…Although treatment could explain this difference, a study reported that the expression and the mean fluorescence intensity of ROR1 were maintained by CLL cells regardless the type of treatment received in GIMEMA trials: ibrutinib + rituximab (CLL1114), venetoclax + rituximab (CLL1518), fludarabine + cyclophosphamide + ofatumumab (CLL0911); ibrutinib + ofatumumab (CLL1215). Particularly, this expression was detected always on residual CLL cells 86 . Transgenic mice expressing both ROR1 and TCL1 developed lymphocytosis and splenomegaly resembling human CLL.…”
Section: Impact Of Ror1 In Signaling Diagnosis and Prognosis Of Cllmentioning
confidence: 92%
“…Particularly, this expression was detected always on residual CLL cells. 86 Transgenic mice expressing both ROR1 and TCL1 developed lymphocytosis and splenomegaly resembling human CLL. In such cells, ROR1 and TCL1, a coactivator of AKT, were found to complex, leading to AKT activation, increased proliferation and resistance to apoptosis.…”
Section: Daneshmanesh Et Al Demonstrated That Anti-ror1 Mouse Mabmentioning
confidence: 99%
See 2 more Smart Citations